Beer spent grains biomass for biogas production: Characterization and anaerobic digestion-oriented pre-treatments. (November 2021) - Carlini, Maurizio; Monarca, Danilo; Castellucci, Sonia; Mennuni, Andrea; Casini, Luca; Selli, Sara
Abstract: The aim of this study focuses on the possibility of producing biogas from brewery spent grains through an anaerobic digestion (AD) process. Beer, in fact, is one of the most consumed drinks all over the world and its highly impactful production process releases a large quantity of wastes, such as spent grains (BSG). In the first part of this work, an energetic characterization of raw BSG has been carried out to define moisture, ashes and volatile solids contents. Then, two pre-treatments of BSG have been analysed, in order to establish how to improve the energetic characteristics of this biomass for an anaerobic conversion process. The first pre-treatment has consisted in a low temperature process, while the second one is an alkali pre-treatment. After the raw biomass has been subjected to each pre-treatment, the energetic characterization has been repeated to evaluate the change of the BSG's properties. The obtained results show that the raw BSG is a suitable biomass for AD application, because of the high content of volatile solids (around 90.9%) and the low percentage of ash on dry basis (about 3.53%). These characteristics has been bettered through the low temperature pre-treatment (volatile solids percentage near 92.7% and ash content approximately equal to 3.59 %) in terms of digestibility by anaerobic digestion reaction, while the alkali one has worsened the volatile solids content (around 73.8%) and increased the ash percentage (near 38.61%).